Skew Cyclic Codes over a Non‐chain Ring. Issue 3 (1st May 2017) - Shi, Minjia; Yao, Ting; Solé, Patrick
Abstract : We study skew cyclic codes over a nonchain ring, which generalizes our previous results in IEICE Trans. on Fundamentals of Electronic Communications and Computer Sciences, 2015. We describe generator polynomials of skew cyclic codes over this ring and investigate the structural properties of skew cyclic codes over the ring by a decomposition theorem. The generator polynomial of the dual code of a skew cyclic code are obtained. Moreover, the idempotent generators of skew cyclic codes are considered. Some examples are also presented to illustrate the discussed results.